2006
DOI: 10.18597/rcog.533
|View full text |Cite
|
Sign up to set email alerts
|

Tipificación del virus del papiloma humano en mujeres con lesión escamosa intraepitelial de bajo grado

Abstract: Objetivo: determinar la prevalencia y los genotipos de los papillomavirus humanos (PVH) en mujeres con lesiones escamosas intraepiteliales de bajo grado (LEIBG).Métodos: noventa y seis mujeres de la clínica de colposcopia fueron incluidas. La presencia del ADN de los PVH en las biopsias fue determinada por ensayo de reacción en cadena de la polimerasa (RCP) con oligonucleótidos para el gen L1. Las muestras fueron coamplificadas con MY09/MY11/HMB01 e iniciadores para betaglobina GH20/PC04. Para tipificar se uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…According to our results, the LSIL's HPV infections were more frequently observed in young women (50%), than in adults (Table 1). Consistent with previously reported results, the highest number of HPV‐positive LSIL cases was in pregnant women between the ages of 18 and 30 16,26–28 . Recent studies have shown that young women have the highest rates of HPV infection (≤25 years, range: 20–35 years), tapering to ≤5% (after age 55) due to low exposure, altered sexual behavior, and acquired immunity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to our results, the LSIL's HPV infections were more frequently observed in young women (50%), than in adults (Table 1). Consistent with previously reported results, the highest number of HPV‐positive LSIL cases was in pregnant women between the ages of 18 and 30 16,26–28 . Recent studies have shown that young women have the highest rates of HPV infection (≤25 years, range: 20–35 years), tapering to ≤5% (after age 55) due to low exposure, altered sexual behavior, and acquired immunity.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previously reported results, the highest number of HPV-positive LSIL cases was in pregnant women between the ages of 18 and 30. 16,[26][27][28] Recent studies have shown that young women have the highest rates of HPV infection (≤25 years, range: 20-35 years), tapering to ≤5% (after age 55) due to low exposure, altered sexual behavior, and acquired immunity. Undoubtedly, the relationship between age and HPV infection has been established, although a synergistic effect of multiple infections has not been observed with the progression of high-risk SIL to CC, where single infections prevail.…”
Section: Discussionmentioning
confidence: 99%